Valuing the Time of the Self-Employed - Daniel Agness; Travis Baseler; Sylvain Chassang; Pascaline Dupas; Erik Snowberg (Center for Economic Studies and ifo Institute (CESifo), 2022)
People's value for their own time is a key input in evaluating public policies: evaluations should account for time taken away from work or leisure as a result of policy. Using rich choice data collected from farming households in western Kenya, we show that households exhibit non-transitive preferences consistent with behavioral features such as loss aversion and self-serving bias. As a result, neither market wages nor standard valuation techniques (such as the Becker-DeGroot-Marschak—BDM—mechanism of Becker et al., 1964) correctly measure participants' value of time. Using a structural model, we identify the mix of behavioral features driving our choice data. We find that these features distort choices when exchanging cash either for time or for goods. Our model estimates suggest that valuing the time of the self-employed at 60% of the market wage is a reasonable rule of thumb.
Keywords: C93; D03; D61; D91; J22; O12; Q12; 330; value of time; non-transitivity; labor rationing; loss aversion; self-serving bias